Agama dalam tentukur antropologi simbolik Clifford Geertz - Yusri Mohamad Ramli, (Universiti Kebangsaan Malaysia, 2012)
Clifford Geertz can be regarded as one of the most influential figures in religious studies, particularly in the field of anthropology. His unique symbolic anthropology approach had attracted researchers because of his emphasis on deductive reasoning in explaining the meaning of religion and in viewing cultural values that exist in religion. Research based on the content analysis of his works found that Clifford Geertz thought very strongly influenced by Ibn Khaldun as both of them emphasize on the practical reality of religious phenomena in the society. These symbols are then making a cultural system of what we call religion.